Criminal Justice and Criminology at the Core: Using a Sustainable Method for Constructing a Core Journal List. Issue 3 (17th November 2021) - Aubele, Joseph; Gardner, Gabriel J.
ABSTRACT: The desire to identify which journals are core to a discipline is important to librarians and departmental faculty alike. Whether for purposes of accreditation, decisions related to retention, tenure, and promotion, or the assessment of a library's collection, core lists are highly valued resources. Applying a previously tested, mixed-methods approach, the authors created a five-tiered list of criminal justice and criminology journals from which 151 titles were identified as being core to the discipline. In an effort to assess the reliability fo their results, the authors also compared the results of their study to a list created by criminal justice scholars.